2012
DOI: 10.1093/ndt/gfs369
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase A1, M1, P1 and T1 null or low-activity genotypes are associated with enhanced oxidative damage among haemodialysis patients

Abstract: According to the GST genotype, ESRD patients may be stratified in terms of the level of oxidative and carbonyl stress that might influence cardiovascular prognosis, but could also improve efforts towards individualization of antioxidant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 53 publications
6
57
2
Order By: Relevance
“…The genotype distribution as well as the frequency of the Ile105Val polymorphism observed in this study did not largely differ from those reported in another Central European population, the Czechs; the variant allele in this group has a reported frequency of 34.4%, and the heterozygote genotype was found to be associated with a decreased risk of colorectal cancer (Hezova et al, 2012). In contrast to our results, the frequency of this allele was higher in a Serbian population, reaching 37.6% (Suvakov et al, 2013). The genotype Ile105Ile frequency observed in our study (41.8%) was similar to that determined by Vichi et al (2012) in a healthy Italian population (42%), where this genotype was found to be associated with a higher risk of endometriosis (frequency in cases, 48.6%).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The genotype distribution as well as the frequency of the Ile105Val polymorphism observed in this study did not largely differ from those reported in another Central European population, the Czechs; the variant allele in this group has a reported frequency of 34.4%, and the heterozygote genotype was found to be associated with a decreased risk of colorectal cancer (Hezova et al, 2012). In contrast to our results, the frequency of this allele was higher in a Serbian population, reaching 37.6% (Suvakov et al, 2013). The genotype Ile105Ile frequency observed in our study (41.8%) was similar to that determined by Vichi et al (2012) in a healthy Italian population (42%), where this genotype was found to be associated with a higher risk of endometriosis (frequency in cases, 48.6%).…”
Section: Discussioncontrasting
confidence: 99%
“…In the 1.67-kb promoter region (with exon 1 fragment) of the human GSTA1 gene, we identified 8 SNPs, including G-52A, C-69T, A-513G, T-567G, G-631T, A-1066T, G-1142C, and G-1245A, confirming the results of Bredschneider et al (2002) in Caucasians, except for the SNP that was only observed in our study at site -1245. The frequency of the GSTA1*B allele containing 3 linked basic variants affecting gene expression (-52A, -69T, -567G) observed in our study among 160 individuals (43.1%) was slightly lower than that observed by Bredschneider et al (2002) among 48 subjects (47.9%), but showed some similarities, including genotype distribution, to the data of global studies in the Caucasian population (38-50%) (Coles et al, 2001;Spalletta et al, 2012;Suvakov et al, 2013). However, in African-American, Japanese, and Chinese subjects, the allele frequency was much lower, at 26, 16, and 12.9%, respectively (Coles et al, 2001;Matsuno et al, 2004;Ping et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…GSTM1 and GSTT1 polymorphism were identified by PCR, while GSTA1 and GSTP1 were identified by restriction fragment length polymorphism PCR (RFLP-PCR) method as previously described (Suvakov et al 2013). …”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…It has been shown that polymorphic expression of GSTs is associated with the altered xenobiotics detoxification efficiency, thus influencing an individual's susceptibility to carcinogens and various diseases (Di Pietro et al 2010;Suvakov et al 2013;Eslami and Sahebkar 2014;Kim et al 2015). Still, there are no data regarding the association between GST genetic polymorphism and bladder cancer risk, neither in patients with BEN, nor in individuals who originate from BEN regions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GSTA1 serves as a crucial role in the GSH binding reaction. In normal liver and kidney tissues, GSTA1-encoded dimeric protein expression is high and serves an important role in the anti-oxidative defense system (14). It is able to catalyze many xenobiotics, such as carcinogens, environmental toxins and certain pharmacological agents, by combining with GSH to promote the degradation of these substances (15).…”
Section: Introductionmentioning
confidence: 99%